State of reduced potential of glutathione and lipid peroxidation in tear of extended wear soft contact lens wearers (Ukrainian Journal of Ophthalmology, 2026)
Background. Contact lens wearing is connected with microtraumatism of the corneal epithelium and the presence of hypoxia in anterior eye tissues.Purpose. To study values of the oxidation-reduction potential and markers of lipid peroxidation in the tear of extended wear soft contact lens wearers.Material and Methods. Patients were divided into two groups: Study Group, 20 patients (40 eyes) with mild/moderate myopia with extended soft contact lens wear; Control Group, 13 patients (24 eyes) with mild/moderate myopia, spectacles wearers. Results.  A level of reduced glutathione in Study Group was by 18.3% lower than that in Control Group (p
Keywords: myopia; soft contact lens; cornea; glutathione; lipid peroxidation; malondialdehyde; diene conjugates